Belimumab or anifrolumab for systemic lupus erythematosus? A risk-benefit assessment - Kirou, Kyriakos A.; Dall`Era, Maria; Aranow, Cynthia; Anders, Hans-Joachim (Frontiers in Immunology, 2022)
Treatment of systemic lupus erythematosus (SLE) currently employs agents with relatively unselective immunosuppressive properties. However, two target-specific biological drugs have been approved: belimumab (anti-B-cell-activating factor/BAFF) and anifrolumab (anti-interferon alpha receptor-1/IFNAR1). With the goal of encouraging and enabling a more informed approach to SLE management, we performed a comparative risk-benefit assessment considering the respective strengths and weaknesses in terms of safety and efficacy. Due to differences in target expression sites, anti-IFNAR1, but not anti-BAFF, might elicit organ-specific effects, consistent with clinical efficacy data. The IFNAR1 is specifically involved in innate and adaptive antiviral immunity in most cells of the body, thus anti-IFNAR1 modulates SLE activity at the cost of impairing host defense to recurrent, persistent, and novel viral exposures. Consistent with this observation, the available safety data suggest an increased risk for some viral infections such as varicella zoster and perhaps influenza. How anti-IFNAR1 affects risk for diseases related to other persistent viruses such as EBV, HIV, HBV or HPV will require longer studies. In addition, anti-IFNAR1 should affect immune responses to novel viruses or novel viral vaccines, although data are still lacking. BAFF is specifically involved in adaptive immune responses in lymphoid tissues, thus anti-BAFF therapy modulates SLE activity without interfering with local innate host defense mechanisms and should only marginally affect immune memory to previous pathogen exposures consistent with the available safety data. Anti-BAFF should also affect immune responses to novel pathogens or vaccines. Clinical trials of both anti-IFNAR1 and anti-BAFF excluded participants with chronic infections including HIV, HBV, and HCV. Risks and benefits to individual patients must be considered as the specific potencies and benefits of anti-IFNAR1 may outweigh these safety concerns, e.g., in patients with disabling musculoskeletal and cutaneous LE manifestations refractory to other treatments and seronegative for persistent viruses.